Intoxication acute per carbamate in the Centre of Health Miguel Grau Chaclacay Lima 2003 - 2007 - Crispín P., Victor (2008)
In Chaclacayo, district (Lima) and around areas they use rodenticide product of free sale. The objective of this study was to describe the acute intoxication cases that frequently arrive to C. S. M. Grau for treatment. We describe 88 retrospective cases of intoxicactions by carbamate happened since 2003 to 2007. We obtanined information from Emergency Book and Clinic Histories The intoxications were all oral and there was not information about the toxic dose. It was no possible to analize the product residue in blood sample. All cases presented moderate to severe intoxication grade and presented abdominal pain, disorientation, nausea, vomiting, disartria, myosis, respiratory distress with bronchorrhea, cough, diaphoresis, sialorrea, shedding tears, flacddity and fasciculation. Of all cases, 35 were men (40%) and 53 were women (60 %), 6 were under the age of 10 (7%),32 were adolescents (35%), 49 were adults from 20 to 59 years old (56%). In infants the intoxication was accidental; in adolescents it was due to their sentimental problems and family hardships, and in adults because of their economic problems.Treatments included gastric lavage in all patients, intravenous hidratation and atropine i.v., There was one deceased before arrive and all patients was recuperated.